Relation of peritumoral, prepectoral and diffuse edema with histopathologic findings of breast cancer in preoperative 3T magnetic resonance imaging - Akdoğan Gemici, Ayşegül; Tokgoz Ozal, Safiye; Hocaoğlu, Elif; Arslan, Gözde; Sen, Ebru; Altınay, Serdar; İnci, Ercan (Journal of Surgery and Medicine, 2019)
Aim: Preoperative breast magnetic resonance imaging (MRI) findings can provide rich information about the prognosis of the disease. Morphologic and dynamic features are especially used for it. We aimed to compare peritumoral, prepectoral, and diffuse edema identified in MRI with histopathologic findings, and to show how prognostic information can be gathered from the identification of edema. Methods: We conducted a retrospective cohort study with forty-six women who underwent breast DCE-MRI as part of the pre-surgical evaluation between January and August 2018 were included in the study. Signal enhancements similar to water that were localized to the prepectoral or peritumoral areas or diffuse enhancements on T2A-weighted sequences were considered as edema. The presence of edema was compared with clinicopathologic parameters such as cancer type, tumor size, histologic grade, ER-PR receptor positivity, Her2 positivity, Ki-67 labelling index and lymphovascular invasion. Results: The mean age of the participants was 53.15±11.75 (range, 27-80) years. Eleven patients had diffuse edema, 27 patients had peritumoral edema, and 5 patients had prepectoral edema. Nineteen luminal A cancers, 17 luminal B, 9 triple-negative, and 1 Her2 cancer were seen. Peritumoral edema was associated with lymphovascular invasion positivity (p=0.002). Tumor size and the level of Ki-67 was associated with peritumoral edema (p=0.001, p=0.009). The odds of observing prepectoral edema showed no statistically significant difference in the presence of lymphovascular invasion positivity and other parameters. The presence of diffuse edema showed significant differences depending on tumor size measurements (p=0.026). Conclusion: Edema in breast MRI can provide information about histopathologic findings, particularly about lymphovascular invasion. The authors suggest that different edema types could be mentioned in radiology reports as a matter of routine given that such findings can provide information about the prognosis.